1992
DOI: 10.1111/j.1365-2621.1992.tb08093.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Flatulence‐Causing Sugars by High Temperature Extrusion of Pinto Bean High Starch Fractions

Abstract: Pinto bean high starch fractions were extruded using a Wenger TX-52 twin screw extruder. The effect of process temperature and moisture in the barrel on flatulence-causing sugars was investigated. Levels of flatulence causing sugar were lower in extruded compared to nonextruded samples with higher reduction at higher process temperature. Sugar content decreased from 5.29% in nonextruded samples to 3.69% in samples extruded at 163°C. Moisture content in the extruder barrel did not significantly affect sugars in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 11 publications
3
28
0
Order By: Relevance
“…moisture (17%) used. Borejszo and Khan (1992) reported that the raffinose and stachyose concentrations in pinto bean flours were reduced by extrusion processing. Berrios and Pan (2001) and Berrios et al (2002) reported that extrusion processing reduced the total oligosaccharide levels in black bean flours and that the extent of their reduction depended on the extrusion conditions employed.…”
Section: Lentilmentioning
confidence: 98%
“…moisture (17%) used. Borejszo and Khan (1992) reported that the raffinose and stachyose concentrations in pinto bean flours were reduced by extrusion processing. Berrios and Pan (2001) and Berrios et al (2002) reported that extrusion processing reduced the total oligosaccharide levels in black bean flours and that the extent of their reduction depended on the extrusion conditions employed.…”
Section: Lentilmentioning
confidence: 98%
“…Soybean oligosaccharides are also very important nutritional components of this food but have been regarded as undesirable components causing flatulence (Borejszo and Khan 1992;Omosaiye et al 1978). They have recently been found to be ''probiotic material'' and have been approved by the Food and Drug Administration as generally recognized safe material in the USA (Hoover 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The action of heat, water and high pressure in an extrusion process may induce desirable chemical changes in the material (Borejszo & Khan, 1992). Benefits of beans extrusion-cooking are deactivation of heat labile growth inhibitors (Aguilera, Crisafulli, Lusas, Uebersax, & Zabik, 1984).…”
Section: Introductionmentioning
confidence: 99%